The MicroRNAs-Transcription Factors-mRNA Regulatory Network Plays an Important Role in Resistance to Cold Stress in the Pearl Gentian Grouper - Miao, Ben-Ben; Niu, Su-Fang; Wu, Ren-Xie; Liang, Zhen-Bang; Zhai, Yun (Frontiers in Marine Science, 2022)
Pearl gentian grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) is a hybrid fish with high commercial value. It is widely cultured on the Asian coast; however, it is not cold-tolerant. Although we have previously characterized the liver transcriptomic responses of this grouper to cold stress, the roles of miRNAs and transcription factors (TFs) in cold resistance and the underlying regulatory mechanisms are still unclear. In this study, we integrated miRNA and mRNA sequencing data for pearl gentian grouper under cold stress and constructed a miRNA-TF-mRNA regulatory network. Furthermore, we screened seven key miRNAs (i.e., gmo-miR-221-5p, ssa-miR-7132b-5p, ola-let-7c, ssa-miR-25-3-5p, ccr-miR-489, gmo-miR-10545-5p, ccr-miR-122) that regulated target genes (including TF ACSS2, TF PPARD, TF PPP4CB; CYP2J2, EHHADH, RXRs, NR1D2, PPP1CC-A, PPP2R1A, FOXK2, etc.). These miRNAs participated in several important pathways and biological processes by the direct or indirect regulation of target genes, such as antioxidation and membrane fluidity, glucose and lipid metabolism, circadian rhythm, DNA repair, and apoptosis. The key cold-related miRNAs, TFs, and genes and their potential regulatory relationships identified in this study provide a deeper understanding of the complex molecular basis of the response to low-temperature environments in the grouper. In particular, our results provide the first identification for the role of NR1D2 gene in the cold tolerance of fish via the regulation of circadian rhythm. Furthermore, the key miRNAs and genes provide a basis for the molecular breeding of new cold-tolerant varieties of the pearl gentian grouper.